Effect of Red Ginger (Zingiber officinale Rubrum) Extract on Chemical and Microbiological Characteristic of Goat Milk Yoghurt - Lita Lianti; Febryos Pernandes Sinaga; Dina Fitryani (UNIVED Press, Dehasen University Bengkulu, 2023)
Goat’s milk consumption (9.6 litre/capita/year) by Indonesian is still lower than cow’s milk consumption (11.8 6 litre/capita/year). One of the causes is because the goaty flavour in goat’s milk. Yoghurt is increasingly in demand, especially for people with lactose intolerance. Yoghurt is preffered because of its probiotics. Innovation in adding red ginger extract in goat milk yoghurt processing is expected can increase public interest in goat’s milk consumption. Besides being able to decrease the goaty flavour, red ginger extract could have more health benefits because of its bioactive contents. This study analysed fermentation time’s effect on the chemical and microbiological characteristics goat’s milk yoghurt (YSK) and goat’s milk yoghurt with red ginger extract (YSK EJM). This study is designed with Randomized Group Design (RGD). The first factor (A) is a different type of yoghurt, namely A1=goat's milk yoghurt without added red ginger extract and A2=goat's milk yoghurt with red ginger extract. The second factor (B) is the fermentation time (P1= 0 hours, P2= 6 hours, P3= 12 hours, P4= 18 hours, and P5= 24 hours. Data were obtained by two replications and two repititions. Ph and total titrated acid between YSK and YSK EJM were significantly different (p<0.05) after 12 hours fermentation. Total Lactic Acid Bacteria (LAB) for the two variations were different after 18 hours fermentation. Total LAB reached 106 CFU/ml for 12 hours fermentation and continuesly increased for 24 hours fermentation, YSK (5.32 x 107 CFU/ml) and YSK EJM (2.83 x 107 CFU/ml).